The effect of sugar addition on the physical properties of milk concentrates and the fouling of equipment – Investigations at lab and pilot-scales - Maurício, Érica Felipe (2021)
Dairy products are highly consumed due to their high nutritional value and pleasant taste. One of the processes that milk can undergo is concentration, which provides some benefits, such as an increase in shelf life and a reduction in transport costs. In addition, the addition of sugar to milk is intended to create a new product, for example, dulce de leche and condensed milk, also increases the product's added value. The addition of sugar to milk generates significant processing changes for the product when compared to pure milk. These differences range from physicochemical properties to the formation of deposits in the heat exchanger. These changes must be considered in the development of new products, especially with the growing consumer demand for products with lower sugar content. According to recent studies, it was possible to observe through methods such as energy dispersive spectroscopy, Raman spectroscopy and scanning electronic microscopy that the reduction of sugar in dulce de leche leads to significant changes in the quantity and composition of deposits formed over the dulce de leche manufacture period using the atmospheric pressure concentration process. This factor directly affects the aspect of industrial cleaning, requiring more attention in terms of time and specific products. Vacuum concentration is usually studied in large evaporators that consume large volumes of milk, being an impediment to research and development tests. Therefore, in this study, two different scales were used – pilot and laboratory, for the manufacture of two dairy products (without addition of sucrose and with the addition of 20% (m·m -1 ) of sucrose). And the formed products were analyzed in relation to the parameters of viscosity, density and surface tension. By observing these three parameters, it was possible to verify that there was no significant difference between the manufacturing scales. Therefore, the products manufactured in them are similar and possible to be studied on a smaller scale. This favors not only the cost reduction aspect for the industry, but also the reduction of environmental impacts, since it reduces water consumption and disposal of organic matter, for example.Keywords: Dulce de leche. Concentrated milk. Sweetened condensed milk.